Papain-Decorated Mucopenetrating SEDDS: A Tentative Approach to Combat Absorption Issues of Acyclovir via the Oral Route - Arshad Mahmood; Rabbia Haneef; Ahmad Z. Al Meslamani; Mohammad F. Bostanudin; Muhammad Sohail; Muhammad Sarfraz; Mosab Arafat (MDPI AG, 2022)
The aim of the current study was to enhance the oral bioavailability of Acyclovir (ACV) based on the papain-functionalized self-emulsifying drug delivery systems (SEDDS). The optimum control SEDDS formulation comprised of kolliphore (40%), transcutol (30%), propylene glycol (20%) and oleoyl chloride (10%). However, in the targeted SEDDS formulation, oleoyl chloride was replaced with oleoyl chloride-papain (OC-PAP) conjugate that was synthesized via an amide bond formation between the acyl halide groups of oleoyl chloride and the amino group of papain. Prior to adding in the SEDDS formulation, the newly synthesized conjugate was evaluated quantitatively by a Bradford assay that demonstrated 45 µg of papain contents per mg of the conjugate. Moreover, the conjugate formation was qualitatively confirmed through FTIR analysis and thin layer chromatography. ACV (a BCS class III drug) was incorporated into the SEDDS formulations after being hydrophobically ion paired with sodium deoxycholate, thereby making it lipophilic. The drug-loaded formulations were emulsified in the 0.1 M phosphate buffer (pH 6.8) and evaluated in vitro with respect to drug release and rabbit mucosal permeation studies. Both the formulations illustrated a very comparable drug release over a period of 4 h, afterwards, the OC-PAP-based formulation demonstrated a more sustaining effect. The extent of mucus diffusion evaluated via the silicon tube method demonstrated a 4.92-fold and a 1.46-fold higher penetration of the drug, a 3.21-fold and a 1.56-fold higher permeation through the rabbit intestinal mucus layer, and a 22.94-fold and a 2.27-fold higher retention of the drug over the intact mucosa of rabbit intestine, illustrated by OC-PAP-based nanoemulsions compared to the drug-free solution and controlled nanoemulsion, respectively. According to these in vitro results, papain-functionalized SEDDS is a promising approach for the oral delivery of ACV and many other drugs with oral bioavailability issues, however, in vivo studies in this respect have to be employed before making a comprehensive conclusion.